Digital dividends in rural China: unraveling the spatio-temporal dynamics of technological progress-driven transformation - Luo, Hanxiang; Xie, Tianwei; Xiang, Zhaoyang (Frontiers in Sustainable Food Systems, 2025)
IntroductionThis study investigates how the digital economy drives rural revitalization in China through technological progress. With the rapid growth of China’s digital economy, understanding its role in promoting rural revitalization has become increasingly important. This study explores the mechanisms through which digital development contributes to rural revitalization, emphasizing the mediating role of agricultural technological progress.MethodsUsing panel data from 281 prefecture-level and above cities from 2011 to 2021, both static and dynamic econometric models are constructed to evaluate the effects of digital economy development. Agricultural technological progress—including general progress, frontier innovation, and pure technical efficiency—is incorporated as both a moderating and threshold variable.ResultsThe results indicate that the digital economy significantly promotes rural revitalization, exhibiting clear spatial and temporal heterogeneity. Among the three dimensions of technological progress, improvements in pure technical efficiency exert the strongest positive effect. Furthermore, threshold analysis shows that as technical efficiency improves, the positive influence of the digital economy intensifies, whereas the effect weakens when general or frontier technological advancement reaches higher levels.DiscussionThese findings highlight the crucial role of agricultural technological efficiency in amplifying the benefits of digitalization for rural development. To maximize the digital dividends, policymakers should focus on strengthening rural digital infrastructure, promoting the integration of digital tools with agricultural technologies, and designing differentiated policy interventions tailored to the stages of technological development.